Groundwater dominates snowmelt runoff and controls streamflow efficiency in the western United States - Paul D. Brooks; D. Kip Solomon; Stephanie Kampf; Sara Warix; Carleton Bern; David Barnard; Holly R. Barnard; Gregory T. Carling; Rosemary W. H. Carroll; Jon Chorover; Adrian Harpold; Kathleen Lohse; et al. (Communications Earth & Environment)
Abstract Climate change in seasonally snow-covered mountain catchments is reducing water supply and decreasing streamflow predictability. Here, we use tritium age dating to show that contrary to the common assumption that snowmelt quickly contributes to runoff, streamflow during snowmelt in western US catchments is dominated by older groundwater. The average age of streamwater during snowmelt runoff (5.7 ± 4.3 years) was intermediate to the average age of groundwater (10.4 ± 4.5 years) and recent precipitation, indicating that 58% (±34%) of snowmelt runoff was derived from groundwater. Water ages, streamflow, and groundwater storage were mediated by bedrock geology: low-permeability hard rock/shale catchments exhibited younger ages, less storage, and more efficient streamflow generation than high-permeability sandstone/clastic catchments. Our results demonstrate that snowmelt runoff is the result of multiple prior years of climate mediated by groundwater storage. Including these interactions will be crucial for predicting water resources as climate and landscape changes accelerate.